RHETORIC AND REALITY - Patterson, Heather (My University, 2001)
Canadians and their politicians have been talking about child care for many years. What has been said and what has been accomplished are very different. This thesis discusses the way politicians have spoken of and dealt with the demands of child care advocates for nationally funded and regulated child care of high quality and universal accessibility. The author argues that neither ofthe two ruling federal political parties, the Liberals and Progressive Conservatives, have ever intended, despite their party platform promises and leaders’ claims, to deliver a national child care program. The thesis follows the political rhetoric surrounding the issue from the delivery ofthe Report the Royal Commission on the Status ofWomen to the end ofthe 2000 election and deals specifically with the political dialogue ofthe 1984, 1993, and 2000 elections.